High-resolution integrated stratigraphy of the OAE1a and enclosing strata from core drillings in the Bedoulian stratotype (Roquefort-La Bédoule, SE France). (September 2015) - Moullade, Michel; Tronchetti, Guy; Granier, Bruno; Bornemann, André; Kuhnt, Wolfgang; Lorenzen, Janne
Abstract: In 2009 two wells were drilled with 100% core recovery at Roquefort-La Bédoule (Bouches-du-Rhône, SE France), the historical Bedoulian stratotype. Here we present holostratigraphic results based on a detailed study of the cored sediments. Our work confirms that the La Bédoule area offers one of the best records for the period spanning the late Bedoulian, the anoxic event OAE1a and the Bedoulian/Gargasian (lower-upper Aptian substages) transition. New data provide a refined succession of micropaleontogical events already well correlated with ammonites from previous fieldwork and, thus, improve the cross-calibration of bioevents with high-resolution isotope stratigraphy. Methods of the quantitative micropalaeontology applied on benthic foraminifera such as tritaxias help testing their probable orbitally triggered cyclicity, which might be used to precise estimates of duration of events such as OAE1a, the Dufrenoya furcata ammonite Zone, the Globigerinelloides ferreolensis planktonic foraminiferal zone and the C7 isotopic stage. The lithologic, biotic and possibly isotopic changes seen at the level of and around bed 170 (top of "Niveau Blanc" sensu auctorum ) are strong arguments to use this key-level as the boundary between the two Aptian substages (or stages in an alternative classification) and to support the proposal of La Bédoule as a potential locality for the GSSP of the Gargasian Substage (or of historical Aptian sensu stricto, in the alternative classification).